Cancer control in Latin America and the Caribbean: recent advances and opportunities to move forward. Issue 11 (November 2021) - Barrios, Carlos H; Werutsky, Gustavo; Mohar, Alejandro; Ferrigno, Ana S; Müller, Bettina G; Bychkovsky, Brittany L; Castro E, Carlos José; Uribe, Claudia J; Villarreal-Garza, Cynthia; Soto-Perez-de-Celis, Enrique; Gutiérrez-Delgado, Francisco; Kim, Ji Seok; et al.
Summary: The increasing burden of cancer represents a substantial problem for Latin America and the Caribbean. Two Lancet Oncology Commissions in 2013 and 2015 highlighted potential interventions that could advance cancer care in the region by overcoming existing challenges. Areas requiring improvement included insufficient investment in cancer control, non-universal health coverage, fragmented health systems, inequitable concentration of cancer services, inadequate registries, delays in diagnosis or treatment initiation, and insufficient palliative services. Progress has been made in key areas but remains uneven across the region. An unforeseen challenge, the COVID-19 pandemic, strained all resources, and its negative effect on cancer control is expected to continue for years. In this Series paper, we summarise progress in several aspects of cancer control since 2015, and identify persistent barriers requiring commitment of additional resources to reduce the cancer burden in Latin America and the Caribbean.